The key complications of hemophilia and recent advancements in their management: an update - Azhar, Afrisya Adlina Mohd; Raj, Alicia Ann; Izam, Filzah; Mokhtar, Muhmammad Danial; Zakaria, Nur Asfarina Izzati Aziz; Banerjee, Kishore Gopal (International Journal of Research in Medical Sciences, 2021)
Hemophilia A is an X-linked recessive disorder which is due to factor VIII deficiency. It is a life-threatening coagulation disorder leading to complications including hemophilic-arthropathy, development of inhibitors, transfusion-related infections and profound psychosocial impact on the life of the patients. The aim of this study is to analyze the challenges in complications and the latest advancements in managing those complications. A thorough and systemic literature review was done to fulfill the objective of this study. The emergence of hemophilic arthropathy due to repeated symptoms of hemarthrosis is the most frequent complication found in haemophiliacs. Another critical complication, mainly seen in resource-poor settings is the development of lethal and severe bleeding episodes including episodes of intracranial hemorrhage. The development of inhibitors is another major challenge which often adds profoundly to the financial burden faced by hemophilia patients. Another major challenge is acquiring various transfusion-transmitted infections which was particularly more common few decades back. Studies also have revealed that there are myriads of significant psychosocial effects affecting the quality of life of hemophiliacs. Emerging treatments such as gene therapy, non-clotting factor concentrate products and extended half-life therapy can usher a new era in the management and the quality of life in hemophilia patients.